The Influence of the Online Student Facilitator and Explaining (SFAE) Cooperative Learning Model on Learning Outcomes of PAI at SMK Persada, Sukabumi City - Jimatul Arrobi; Endang Supiani; Wida Hartika (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The study aims to determine the effect of the Student Facilitator And Explaining (SFAE) type cooperative learning model through the online system on the learning outcomes of class X Pharmacy 1 in PAI subjects at Persada Vocational High School, Sukabumi City. This type of research is based on a quantitative approach with descriptive and inferential/inductive statistical analysis. The research design was quasi-experimental, matching only the pre-test post-test control group design technique. The research process involved an experimental group (Class X Pharmacy 1) with a sample of 28 students who were given treatment and a control group (Class X Pharmacy 2) with a sample of 27 students who were not given treatment. Data collection techniques were library research, documentation, observation, and tests. The test is in the form of multiple choice, and the description refers to the PAI subject matter "sources of Islamic law". The comparison test results show the value of t = 3.022 > ttable 2.048 which means Ho is accepted and Sig = 0.005 <0.05. Then Ha is received, or there is a significant comparison of learning outcomes between classes X Pharmacy 1 and 2. The pre-test post-test comparison test results for the experimental class show that the value of t = -9.750 < ttable 2.048 and Sig = 0.000 <0.05, then Ho is rejected and Ha is accepted, or there is a significant comparison between the pre-test and post-test values of the experimental class (X Pharmacy). Thus, applying the online Student Facilitator and Explaining (SFAE) cooperative learning model has an effect on increasing PAI students' learning outcomes at SMK Persada, Sukabumi City. Students are more active in digging for information from PAI material sources and are able to rewrite the results of the information they got in the form of concept maps. So that students become much easier to understand the learning material